Conceptual container metaphors and entrapment in Woolf's Mrs Dalloway - Vuković-Stamatović, Milica (Primerjalna književnost, 2018)
This paper deals with conceptual container metaphors in the novel Mrs Dalloway by Virginia Woolf. The study is based on the Conceptual Metaphor Theory (Lakoff and Johnson 1980), as well as on its extended versions which have contributed to the study of conceptual metaphor in literary texts, as proposed by Werth (1994) and Tsur (1999). The focus is on container metaphors suggesting entrapment and containment, identified both through rapid conceptualisation (identification by means of the immediate context) and its delayed counterpart (metaphors discovered bearing in mind the entire text of the novel). We argue that container metaphors in the novel combine into a metaphoric web permeating the entire body of the novel and defining all the characters. This undercurrent of metaphors helps create an atmosphere of entrapment.
Keywords: angleška književnost; hitra konceptualizacija; kognitivna teorija metafore; konceptualna metafora; odložena metafora; omejenost; ujetost; Woolf, Virginia; zapoznela konceptualizacija